Design of a Reduced-Size Crossed-Dipole Antenna - Kedze, Kam Eucharist; Wang, Heesu; Kim, Youngwook; Park, Ikmo (IEEE Transactions on Antennas and Propagation, 2021)
This article proposes two reduced-size crossed-dipole antennas that comprise two printed crossed-dipole arms and a pair of vacant-quarter printed rings to generate circularly polarized (CP) radiation. The T-shaped crossed-dipole antenna is similar to a conventional crossed-dipole antenna but differs that half of the crossed dipole is rotated 90°. This rotation reduces the dipole's area coverage by nearly half, resulting in a compact antenna that generates CP radiation with performance similar to that of a conventional crossed-dipole antenna. A compact folded E-shaped crossed dipole with good CP radiation characteristics is formed by folding the arms of the T-shaped antenna. The performance of these compact reduced-size crossed-dipole antennas is discussed. The T-shaped antenna with an overall radiator size of 30.3 mm × 51.4 mm × 0.508 mm (0.29 λ o × 0.5λo × 0.005λ o at 2.97 GHz) has an S11 < - 10 dB bandwidth of 2.58-3.42 GHz (28%) and a 3 dB AR bandwidth of 2.78-3.16 GHz (12.8%). The folded E-shaped crossed-dipole antenna with overall dimensions of 19.6 mm × 31mm × 0.508 mm ( 0.21λo × 0.33λo × 0.0055λ o at 3.25 GHz) has an S11 < -10 dB bandwidth of 2.92-3.44 GHz (16.4%) and a 3 dB AR bandwidth of 3.06-3.44 GHz (11.7%).
Keywords: Area coverages; Circularly polarized; Compact antenna; Crossed dipoles; Crossed-dipole antenna; E-shaped; Radiation characteristics; Reduced size; Antenna miniaturization; broadband; circular polarization; crossed dipole